(untitled) (Irrigation and Melioration, 2026)
This study advances a rigorous theoretical framework for the sliding cutting mechanism executed by a blade mounted on a rotating roller, with the objective of intensifying the efficiency of soil clod comminution in agricultural systems. Particular emphasis is placed on the kinematic coupling between tangential and angular velocity components of the cutting edge, alongside a detailed examination of contact-point dynamics and the nonlinear influence of a variable cutting radius. The investigation further elucidates the kinematic transformation of the effective sharpening (rake) angle under sliding cutting conditions and its consequent impact on stress-strain localization, fracture initi ation, and the evolution of cutting resistance. It is theoretically substantiated that the superposition of a tangential velocity component induces a transition from predominantly compressive loading to shear-dominated failure mechanisms. This transition significantly reduces the effective tool-material contact interface, amplifies stress concentration, and promotes microcrack nucleation and propagation in low-moisture, brittle soil aggregates. Through analytical modeling and parametric optimization, the study establishes the optimal geometric and kinematic configurations of the blade-roller system, including blade inclination, roller diameter, and translational velocity regimes. The results demon strate that the rational coordination of these parameters yields a pronounced decrease in cutting resistance, enhanced fragmentation uniformity, and a measurable reduction in specific energy con sumption. Overall, the findings provide a mechanistically grounded and quantitatively substantiated basis for the design and optimization of energy-efficient soil tillage implements, thereby contributing to the advancement of sustainable and high-performance agricultural processing technologies.